ANALYSIS COGNITIVE DOMAIN INSTRUMENTS OF EVALUATION IN SMA BANDUNG - sepita ferazona (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2018)
The level of competence achievement will be known by evaluating the students after all the basic competencies that exist in the standard of the content they are studying, which must be seen how the suitability of the evaluation instruments provided to the students with the demands of basic competencies and the process of learning in the class .. The method used in this researchis a descriptive method. Subjects were ten biology teachers from seven SMANs in Bandung as a sample, each school representing three clusters. Selection of this research sample is done by using stratified sampling technique, that is by choosing school with high category, medium and low. KD analyzed material of Class X Plantae and Class X Excression System. Plantae material learning process question and excretion system on cluster 1, the highest average at level C2 (understanding) that is equal to 55,91%. While on cluster 2 the highest average also at level C2 (understanding) that is equal to 50,96%. While on the cluster 3 the highest average is also at level C2 (understand) that is equal to 48,91%. The cognitive domain of Plantae's exercise / material tasks in cluster 1, the highest average at the level C1 (knowledge) is 57.5%. While on the cluster 2 the highest average also at level C1 (knowledge) that is equal to 71,67%. While the highest average cluster is at level C2 (understanding) that is equal to 51,67%. The cognitive domain of Plantae material repetition and Excretion System in cluster 1, the highest average at the level of C1 (knowledge) is 56.67%. While on the cluster 2 average highest at level C1 (knowledge) that is equal to 56,3%. While on the cluster 3 highest cognitive domain is at level C1 (knowledge) that is equal to 52,55%.